2002
DOI: 10.1080/02791072.2002.10399955
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Prevalence of Ecstasy Use Among Juvenile Offenders

Abstract: To date, no studies have examined Ecstasy use among criminal justice populations. Focusing on individuals under criminal justice supervision is useful because "new" illegal drugs will typically take root in a criminal population before diffusing to the general population. In the current study, self-report drug use data and urine specimens were collected from 209 juvenile offenders surveyed through Maryland's Offender Population Urinalysis Screening (OPUS) Program. Prevalence estimates are generated and associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 7 publications
3
14
0
Order By: Relevance
“…Arria et al (2000) reported that ecstasy users recruited from rave settings were more likely to report past experiences with marijuana, cocaine, and other drugs than their nonecstasy using counterparts. Yacoubian et al (2002) and Wish et al (under review) report similar findings in a sample of juvenile offenders and college students, respectively. Although it is apparent that ecstasy users are likely to engage in polysubstance use, little is known about whether these other illicit substances are used before, during, and/or after ecstasy use.…”
Section: Ecstasy and Polysubstance Usesupporting
confidence: 63%
“…Arria et al (2000) reported that ecstasy users recruited from rave settings were more likely to report past experiences with marijuana, cocaine, and other drugs than their nonecstasy using counterparts. Yacoubian et al (2002) and Wish et al (under review) report similar findings in a sample of juvenile offenders and college students, respectively. Although it is apparent that ecstasy users are likely to engage in polysubstance use, little is known about whether these other illicit substances are used before, during, and/or after ecstasy use.…”
Section: Ecstasy and Polysubstance Usesupporting
confidence: 63%
“…found that female users of stimulants (e.g., amphetamine and methamphetamine) were about 3 times as likely as male users to develop stimulant dependence in the past year. Among a sample of juvenile offenders, females were found to be more likely than males to use MDMA (Yacoubian et al, 2002). Investigators in Germany reported that, among a community sample of youths aged 14 to 24, female users of stimulants and/or hallucinogens started their first use at a younger age than male users (von Sydow et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Ecstasy has drawn a moderate amount of scientific attention, with most of the available research focused on the psychopharmacology of the drug. Few studies have directly examined possible links between ecstasy and crime or systematically compared the prevalence of ecstasy in offender and general populations (Yacoubian, 2002).…”
Section: Introductionmentioning
confidence: 99%